Penerapan Search Engine Optimization (SEO) Pada Strategi Digital Marketing UMKM - Sintha Erika Putri; Budi Prabowo (Pusat Riset dan Inovasi Nasional, 2023)
In the current digital era, MSMEs business competition is getting tougher in getting customers through digital marketing platforms. The best strategies and solutions are needed by MSMEs to gain market share by optimizing several search engine techniques. Digital marketing in the form of websites that rank well on Google search pages will get more potential visitors. The website must be capable of being featured on Google pages. One way to optimize a website is by using search engine optimization (SEO) techniques to get a good ranking on search engine pages. SEO techniques are needed to increase brand awareness and generate potential traffic for a company's services or products. In this study, the authors apply SEO to MSMEs engaged in florist business. This research is an implementative research with SEO Web Design Methodology method, which emphasizes the delivery of information precisely and quickly. The result of implementing the system development method carried out on the digital marketing platform software from Funcraft Florist is that the Funcraft.epizy.com website can appear on the initial ranking of Google pages after applying SEO techniques according to keywords.